Multiple forms of glucose-6-phosphate dehydrogenase of Neurospora crassa - M. U. Tsao; M. W. Smith (Fungal Genetics Reports, 1963)
Multiple forms of glucose-6-phosphate dehydrogenase of Neurospora crassa/